Research on awareness of Islamic gold investment account among degree students of Faculty of Business Management in UiTM Segamat, Johor / Noor Syafiqah Zainudin - Zainudin, Noor Syafiqah (2016)
Islamic Gold Investment Account can be considered as a new type of investment which has been introduced by certain financial institution in Malaysia. Gold Investment Account in conventional type also has been introduced by financial institutions in Malaysia and it is quite popular among investors. This kind of investment is following the Shariah principle, so it is great opportunity for Muslims to be involved in Islamic gold investment account. However, this study is only open to final year degree students of faculty business management in UiTM Segamat, Johor with the purpose to determine their awareness level of Islamic gold investment account. This is because it is believed that the early step to make people aware of this investment is by introducing it to the young generation who can help build a great economy in the future. This research used primary data, which questionnaire distributed and data collected from one hundred final year degree students of faculty business management in UiTM Segamat, Johor as a sample for this study. The data has been collected were analysed using Statistical Package for Social Science (SPSS). The finding would provide a clear vision of level awareness of Islamic gold investment account among UiTM Johor degree students in Segamat campus.